Effect of Electroacupuncture on Hyperalgesia and Vasoactive Neurotransmitters in a Rat Model of Conscious Recurrent Migraine. (14th May 2019) - Xu, Xiaobai; Liu, Lu; Zhao, Luopeng; Li, Bin; Jing, Xianghong; Qu, Zhengyang; Zhu, Yupu; Zhang, Yajie; Li, Zhijuan; Fisher, Marc; Cairns, Brain E.; Wang, Linpeng
Abstract : Migraine onset is associated with the abnormal release of vasoactive neurotransmitters from perivascular nerves, and these neurotransmitters are involved in the pathophysiology of migraine. Hyperalgesia is a key feature of migraine, and accumulating evidence indicates that electroacupuncture (EA) at the single acupuncture point (Fengchi [GB20] ) is effective in ameliorating hyperalgesia. In clinical practice, multiple acupuncture points are widely used, especially GB20 and Yanglingquan (GB34). However, the role played by vasoactive neurotransmitters in acupuncture antihyperalgesic effect at the single or multiple acupuncture points remains unknown. We aimed to determine whether EA would exert its antihyperalgesic effects by modulating vasoactive neurotransmitter release from the perivascular nerves. Furthermore, we examined whether targeting multiple acupuncture points would be more effective than targeting a single point in reducing hyperalgesia. The mechanical and thermal hyperalgesia were evaluated by measuring the facial and hind-paw mechanical withdrawal thresholds, tail-flick and hot-plate latencies. Plasma concentrations of vasoactive neurotransmitters were determined using rat-specific ELISA kits from jugular vein, including calcitonin gene-related peptide (CGRP), substance P (SP), vasoactive intestinal peptide (VIP), neuropeptide Y (NPY), pituitary adenylate cyclase-activating polypeptide (PACAP), nitric oxide (NO), and endothelin-1 (ET-1). The result suggested that EA significantly ameliorated the mechanical and thermal hyperalgesia, reduced c-Fos levels in the trigeminal ganglion, and attenuated plasma and dural levels of vasoactive neurotransmitters, especially in the multiple acupuncture points group (GB20+GB34). In conclusion, EA exerts antihyperalgesic effect in a rat model of conscious recurrent migraine, possibly via modulation of the vasoactive neurotransmitters. Furthermore, targeting multiple acupuncture points is more effective than targeting a single point in reducing hyperalgesia.